Self-rated health, and frailty in older adults from the population-based Three-City Bordeaux cohort - Pilleron, S; Le Goff, M; Ajana, S; Feart, C (Karger Publishers, 2021)
Introduction: To investigate the association between self-rated health (SRH) and frailty and its components among community-dwellers aged 75 years and older.